TONELI, Maria Juracy Filgueiras; LAGO, Mara Coelho de Souza; BEIRAS, Adriano; CLIMACO, Danilo de Assis (Org.). Atendimento a homens autores de violência contra as mulheres: experiências latinoamericanas. - Barcellos, Wanda Beatriz Elsen (Revista Estudos Feministas, 2013)
TONELI, Maria Juracy Filgueiras; LAGO, Mara Coelho de Souza; BEIRAS, Adriano; CLIMACO, Danilo de Assis (Org.). Atendimento a homens autores de violência contra as mulheres: experiências latinoamericanas.